2014
DOI: 10.1155/2014/130894
|View full text |Cite
|
Sign up to set email alerts
|

A Role for T-Lymphocytes in Human Breast Cancer and in Canine Mammary Tumors

Abstract: Chronic inflammation in the tumor microenvironment has a prominent role in carcinogenesis and benefits the proliferation and survival of malignant cells, promoting angiogenesis and metastasis. Mammary tumors are frequently infiltrated by a heterogeneous population of immune cells where T-lymphocytes have a great importance. Interestingly, similar inflammatory cell infiltrates, cytokine and chemokine expression in humans and canine mammary tumors were recently described. However, in both species, despite all th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 93 publications
3
58
2
Order By: Relevance
“…Our data are according to results that the carcinomas with high lymphocytic infiltrate exhibited shorter overall survival [2]. Besides, the high lymphocytic infiltrate can be associated with other poor prognostic factors, such as high histological grade, lymphatic invasion, and necrosis [16].…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…Our data are according to results that the carcinomas with high lymphocytic infiltrate exhibited shorter overall survival [2]. Besides, the high lymphocytic infiltrate can be associated with other poor prognostic factors, such as high histological grade, lymphatic invasion, and necrosis [16].…”
Section: Discussionsupporting
confidence: 71%
“…In the present study, it was observed that FoxP3+ labeling were distributed in the intratumoral region and in the inflammatory infiltrate. The increase of Treg in the tumor microenvironment may be related to factors of poor prognosis of mammary carcinomas, such as high histological grade, lymphatic invasion and necrosis, and lower survival rates for animals [2,16]. In addition, it has been suggested that Treg play a key role in the development of these tumors, since it would be linking immune suppression with tumor angiogenesis, together in the same biological program [1].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations